The sex‐shift in single disease and multimorbid asthma and rhinitis during puberty ‐ a study by MeDALL. Issue 3 (7th November 2017) - Keller, T.; Hohmann, C.; Standl, M.; Wijga, A. H.; Gehring, U.; Melén, E.; Almqvist, C.; Lau, S.; Eller, E.; Wahn, U.; Christiansen, E. S.; von Berg, A.; et al.
Abstract: Background: Cross‐sectional studies suggested that allergy prevalence in childhood is higher in boys compared to girls, but it remains unclear whether this inequality changes after puberty. We examined the sex‐specific prevalence of asthma and rhinitis as single and as multimorbid diseases before and after puberty onset in longitudinal cohort data. Methods: In six European population‐based birth cohorts of MeDALL, we assessed the outcomes: current rhinitis, current asthma, current allergic multimorbidity (ie, concurrent asthma and rhinitis), puberty status and allergic sensitization by specific serum antibodies (immunoglobulin E) against aero‐allergens. With generalized estimating equations, we analysed the effects of sex, age, puberty (yes/no) and possible confounders on the prevalence of asthma and rhinitis, and allergic multimorbidity in each cohort separately and performed individual participant data meta‐analysis. Findings: We included data from 19 013 participants from birth to age 14‐20 years. Current rhinitis only affected girls less often than boys before and after puberty onset: adjusted odds ratio for females vs males 0.79 (95%‐confidence interval 0.73‐0.86) and 0.86 (0.79‐0.94), respectively (sex‐puberty interaction P  = .089). Similarly, for current asthma only, females were less often affected than boys both before and after puberty onset: 0.71, 0.63‐0.81 and 0.81, 0.64‐1.02, respectively (sex‐puberty interaction P  = .327). The prevalence of allergic multimorbidity showed the strongest sex effect before puberty onset (female‐male‐OR 0.55, 0.46‐0.64) and a considerable shift towards a sex‐balanced prevalence after puberty onset (0.89, 0.74‐1.04); sex‐puberty interaction: P  < .001. Interpretation: The male predominance in prevalence before puberty and the "sex‐shift" towards females after puberty onset were strongest in multimorbid patients who had asthma and rhinitis concurrently.